Tailoring Communications for Primary Care Settings - Rimer, B. K.; Glassman, B. (Methods of Information in Medicine, 1998)
In more and more medical settings, physicians have less and less time to be effective communicators. To be effective, they need accurate, current information about their patients. Tailored health communications can facilitate positive patient-provider communications and foster behavioral changes conducive to health. Tailored communications (TCs) are produced for an individual based on information about that person. The focus of this report is on tailored print communications (TPCs). TPCs also enhance the process of evaluation, because they require a database and the collection of patient-specific information. We present a Tailoring Model for Primary Care that describes the steps involved in creating TPCs. We also provide examples from three ongoing studies in which TPCs are being used in order to illustrate the kinds of variables used for tailoring the products that are developed and how evaluation is conducted. TPCs offer opportunities to expand the reach of health professionals and to give personalized, individualized massages in an era of shrinking professional contact time.
Keywords: Tailored print communications; Primary care; New' media; Cancer screening